The Determinants of the Commitment to Corporate Social Responsibility: Case of Tunisia - Haifa Chtourou Rekik (Journal of Accounting, Business and Management (JABM), 2016)
The purpose of this paper is to highlight the main determinan explainingthe behaviors of Tunisian Companies on Corporate Social Responsibility (CSR). In fact,On the basis of a theoretically constructed questionnaire, We developed two measure ofoverall CSR l\CLiVlty (level of commitment and intensity of commitment) and twomeasures of the C0tnm.itm€ni by CSR action type <pl1Llar|[hr0p1C CSR, integrative CSRand innovative CSR). The estimates were made from an OLS regression analysis i.ti aﬁrst case and from an ordered PROBIT analysis in a second one.The maii-i result that emerges from this study is diat the overall commitment andthe Commitrnent by CSR acuoii type are determined by different factors, withthe exception oi “stakeliolders integration” vaniible which seems to explainthe conimitmeiit in any CSR action type. The industry is Clé‘[€1"I1‘iinnLlV€ only in the caseof philanthropic actions marking a Signiﬁcant commitment of the chemical industry.Philanthropic eornnnnnent is still determined by respondents’ perception of CSRreﬂecting their ethical values, by rirore size and by respondents’ academic training.Integrated commiunent is priinarily determined by the ﬁrnfs age and the F.nti’s CSR respondents’ ages. Finally, g-rowmg companies are the most involved in the LnnovaitiveIREZSREES.